Pengaruh Third Party Funds, Non Performing Financing, dan Financing to Deposit Ratio terhadap Murabahah Financing pada Bank Pembiayaan Rakyat Syariah - Purwita, Anis; Fauzi, Achmad; Susanti, Santi (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2024)
Purpose: The aim of this research is to determine whether Third Party Funds (TPF) influence Murabahah Financing, Non-Performing Financing (NPF) influences Murabahah Financing, Financing to Deposit Ratio (FDR) influences Murabahah financing, and Third Party Funds (TPF), Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR) influence Murabahah financing at BPRS in Indonesia for the 2023 period. Research methodology: This type of research is quantitative and uses associative analysis. The data used is Secondary data were obtained from the financial statements of the Sharia People's Financing Bank (BPRS) and the annual financial ratio from the Financial Services Authority (OJK) website. The sampling technique used purposive sampling by determining the criteria so that 145 BPRS were obtained as samples. Data analysis techniques consisted of descriptive statistics, analysis requirements tests (Normality Test and Linearity Test), Classical Assumption Test (Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test), Multiple Linear Regression, T Test, F Test, and Correlation Coefficient and Determination Test. Statistical analysis was performed using SPSS 25. Results: Based on the research results, it can be concluded (1) Partially. TPF has a positive and significant effect on murabahah financing in the BPRS Indonesia for the period 2023. (2) Partially, NPF has a negative and significant effect on murabahah in the Indonesian BPRS in 2023. (3) Partial FDR has a positive and significant effect on murabahah in the Indonesian BPRS for the period 2023. (4) TPF, NPF, and FDR have a significant influence on murabahah financing in BPRS Indonesia for the 2023 period. Limitations: The limitation of this study is that there are many factors that affect Murabahah financing, but the researcher only takes three factors: Third Party Funds (TPF), Non-Performing Financing (NPF), and Financing To Deposit Ratio (FDR). No independent variables or moderation effects were included. Contribution: This research is useful for Islamic People's Financing Banks (BPRS), which aim to analyze customer eligibility, avoid congestion, and reduce financing risks. Thus, in the future, the BPRS can maximize other financing products.